A systematic review of advanced endoscopy-assisted lithotripsy for retained biliary tract stones: laser, electrohydraulic or extracorporeal shock wave - Veld, Joyce V.; van Huijgevoort, Nadine C. M.; Boermeester, Marja A.; Besselink, Marc G.; van Delden, Otto M.; Fockens, Paul; van Hooft, Jeanin E. (Endoscopy, 2018)
Background When conventional endoscopic treatment of bile duct stones is impossible or fails, advanced endoscopy-assisted lithotripsy can be performed by electrohydraulic lithotripsy (EHL), laser lithotripsy, or extracorporeal shock wave lithotripsy (ESWL). No systematic review has compared efficacy and safety between these techniques. Methods A systematic search was performed in PubMed, the Cochrane Library, and EMBASE for studies investigating EHL, laser lithotripsy, and ESWL in patients with retained biliary tract stones.Results After screening 795 studies, 32 studies with 1969 patients undergoing EHL (n = 277), laser lithotripsy (n = 426) or ESWL (n = 1266) were included. No randomized studies were available. Although each advanced lithotripsy technique appeared to be highly effective, laser lithotripsy had a higher complete ductal clearance rate (95.1 %) than EHL (88.4 %) and ESWL (84.5 %; P  < 0.001). In addition, a higher stone fragmentation rate was reported for laser lithotripsy (92.5 %) than for EHL (75.5 %) and ESWL (89.3 %; P < 0.001). The post-procedural complication rate was significantly higher for patients treated with EHL (13.8 %) than for patients treated with ESWL (8.4 %) or laser lithotripsy (9.6 %; P = 0.04). Data on the recurrence rate of the biliary tract stones were lacking. Conclusion This systematic review revealed that laser lithotripsy appeared to be the most successful advanced endoscopy-assisted lithotripsy technique for retained biliary tract stones, although randomized studies are lacking.